Synthesis, electrochemical properties, and antioxidant activity of sterically hindered catechols with 1,3,4-oxadiazole, 1,2,4-triazole, thiazole or pyridine fragments - Burmistrova, Daria A.; Galustyan, Andrey; Pomortseva, Nadezhda P.; Pashaeva, Kristina D.; Arsenyev, Maxim V.; Demidov, Oleg P.; Kiskin, Mikhail A.; Poddel’sky, Andrey I.; Berberova, Nadezhda T.; Smolyaninov, Ivan V. (Beilstein Journal of Organic Chemistry, 2024)
A series of new RS−, RS−CH2− and R2N−CH2-functionalized сatechols with heterocyclic fragments such as 1,3,4-oxadiazole, 1,2,4-triazole, thiazole, or pyridine were synthesized by the reaction of 3,5-di-tert-butyl-o-benzoquinone or 3,5-di-tert-butyl-6-methoxymethylcatechol with different heterocyclic thiols. The S-functionalized catechols were prepared by the Michael reaction from 3,5-di-tert-butyl-o-benzoquinone and the corresponding thiols. The starting reagents such as substituted 1,3,4-oxadiazole-2-thiols and 4H-triazole-3-thiols are characterized by thiol–thione tautomerism, therefore their reactions with 3,5-di-tert-butyl-6-methoxymethylcatechol can proceed at the sulfur or nitrogen atom. In the case of mercapto-derivatives of thiazole or pyridine, this process leads to the formation of the corresponding thioethers with a methylene linker. At the same time, thiolated 1,3,4-oxadiazole or 1,2,4-triazole undergo alkylation at the nitrogen atom in the reaction with 3,5-di-tert-butyl-6-methoxymethylcatechol to form the corresponding thiones. The yield of reaction products ranges from 42 to 80%. The crystal structures of catechols with 3-nitropyridine or 1,3,4-oxadiazole-2(3H)-thione moieties were established by single-crystal X-ray analysis. The possibility of forming intra- and intermolecular hydrogen bonds has been established for these compounds. The electrochemical behavior of the studied compounds is influenced by several factors: the nature of the heterocycle and its substituents, the presence of a sulfur atom in the catechol ring, or a thione group in the heterocyclic core. The radical scavenging activity and antioxidant properties were determined using the reaction with synthetic radicals, the cupric reducing antioxidant capacity assay, the inhibition process of superoxide radical anion formation by xanthine oxidase, and the process of lipid peroxidation of rat liver (Wistar) homogenates in vitro.
Keywords: antioxidant activity; catechol thioethers; heterocycles; redox-transformations; thiones